Business ethics cases and decision models: A call for relevancy in the classroom - Mathison, David L. (1988)
Classroom cases and decision making models used in the teaching of business ethics may be inconsistent with the actual needs of practicing manager students. Three summary cases written by practicing manager students are included in this paper as well as evidence that concerns a focus more on interpersonal dilemmas rather than top management decisions. As well, the relevancy of philosophical perspectives of ethical decision models is questioned. More practical, hands-on models for ethical decisions are provided. Finally, conclusions of relevancy for the field are drawn.
Keywords: Management Decision; Business Ethic; Practice Manager; Economic Growth; Decision Making